Presuppositions of (Human Movement) Science - Woudenberg, René van (Escuela de Educación Física y Deportes - Universidad de Costa Rica, 2017)
This paper argues that science, human movement science included, proceeds from many presuppositions. First, it explains what sorts of things presuppositions are. Next, it argues that science proceeds from metaphysical, epistemic, and normative presuppositions. The argument entails that neither scientism nor Naturalism is a presupposition of science.